Development, sensory profile and physicochemical properties of jabuticaba nectar with lyophilized jussara pulp - Suemitsu, Laura; Inada, Kim; Fernandes, Paula; Perrone, Daniel; Monteiro, Mariana; Melo, Lauro (Revista Ciência Agronômica, 2020)
Jabuticaba and jussara are both fruits from the Brazilian Atlantic Forest and endangered plant species due to their unsustainable exploitation. In order to protect these plants, it is important to develop products made with these fruits. We have developed a ready-to-drink jabuticaba nectar with the addition of lyophilized jussara pulp (LJP) applying sensory tests, such as acceptance test and Check-All-That-Apply (CATA). Optimal sensory conditions ranged between 150 g L-1 and 200 g L-1 for sucrose concentration and between 450 mL L-1 and 550 mL L-1 for jabuticaba pulp concentration. Just-about-right scale showed that the ideal concentration of LJP used as a natural color additive was 7.2 g L-1 (R2=0.99902). Affective test showed that nectars added with LJP had higher acceptance means than samples without the colorant (P0.05). Jabuticaba nectar added with LJP presented high acceptance among consumers (P